Free-Floating Scapular Spine: A Rare Shoulder Injury. (30th September 2019) - Cabot, John H.; Dang, Khang H.; Dutta, Anil K.
Abstract : A specific treatment protocol for managing scapular spine fractures does not currently exist. The purpose of our report is to describe this type of injury and detail our treatment management in order to better elucidate this rare pathology. We present a case of a 26-year-old female with an acute scapular spine and base fracture after a motor vehicle collision. Successful treatment of an acute free-floating scapular spine fracture was achieved with open reduction and internal fixation utilizing an elbow plate. Since scapular spine fractures are an unfortunate, rare injury, it may impose difficult challenges to the treating surgeon. With our case report, we hope to contribute to the overall knowledge of scapular spine fractures and offer our experience with a successful and appropriate treatment option in our patient.